Uji Coba Serbuk Daun Pandan Wangi (Pandanus Amaryllifolius) sebagai Larvasida terhadap Kematian Larva Nyamuk Aedes Aegypti - Amelia, Fitri; Harmani, Nanny (Jurnal Sehat Mandiri, 2023)
Dengue Hemorrhagic Fever (DHF) is an acute viral infectious disease caused by the dengue virus found in the Aedes aegypti mosquito. This mosquito is the fastest growing in the world and infects nearly 390 million people each year. To prevent its development, insecticides such as abate powder are used. Natural insecticides such as fragrant pandan leaves (Pandanus amaryllifolius) to avoid this impact. This study aims to determine the ability of fragrant pandan leaf powder used as a larvicide against the death of Aedes aegypti mosquito larvae. The research method uses an experimental design with a Post-Test Only Control Design. The sample was third instar Aedes aegypti mosquito larvae as many as 25 larvae in each treatment. Fragrant pandan leaves are made in the form of powder which is put into a tea bag, the powder is divided into 3 doses namely 2.5 grams, 3 grams and 3.5 grams. The analysis used the One way of ANOVA statistical test and the probit test. The results showed that there were differences in the dosage of pandan leaf powder in killing Aedes aegypti mosquito larvae (p value = 0.000). In conclusion, pandan leaf powder can be used as a larvicide in killing Aedes aegypti mosquito larvae. It is recommended that people use fragrant pandan leaf powder as a larvicide and use a higher dose in order to kill 100% of the larvae.